SHIDQ IKHTIBAR AL-QABUUL FII AL JAAMI'AH - Raswan, Raswan (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2015)
This article is result of research on the validity of the college entrance test. College entrance test including programs of study must have the characteristics of a good test especially predictive validity. Entrance test study program Master of Arabic Education (PBA) FITK UIN Jakarta consists of four types of tests; the Academic Potential Test (TPA), TOAFL, TOEFL and interviews, the four must be able to predict exactly when the students join the program. That is, students who earn higher test scores should be able to follow the course as evidenced by the value of IP and or higher GPA compared with the results of the entry test lower. Similarly in predicting students graduate on time, which requires in addition to success in the lecture was also successful in the final project / Thesis which some students a frightening specter. Its mean that students with higher admission tests should be faster in completing the study compared with the lower value of the entry test. If not, then it must be held meta-evaluation of the instruments and implementation of entrance tests which have already become standards.DOI: 10.15408/a.v2i1.1300